Effect of path length on valve tray columns: Experimental study. (14th April 2015) - Brahem, Rim; Royon-Lebeaud, Aude; Legendre, Dominique
Abstract: Experimental measurements of hydrodynamic and interfacial area parameters are carried out over two rectangular pilot scale valve tray columns. The effect of tray path length on extrapolation between the two columns is studied and phenomenological correlations for hydrodynamic and interfacial area are proposed. Correlations are compared both to literature and to industrial results showing good agreement and a significant improvement for the prediction of industrial conditions. Discrepancies preventing an accurate description of industrial trends are highlighted through comparison between typical emulsion height profiles on both columns. Highlights: Hydrodynamic and interfacial area measurements on two different size columns. Phenomenological correlations proposed for key design parameters. A non-negligible effect of the flow path length on mean emulsion profiles.